Application of simulated annealing in logistics vehicle allocation system: A case study from Vietnamese FMCG company - Dao, Le Duc; Chinh, Dao Quang (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2023)
Fast-moving consumer goods (FMCG) are products that sell quickly with a reasonable price. The FMCG business segment is characterized by efficient distribution systems to manage a vast array of products with varying shelf lives and consumer demand patterns. For any FMCG and consumer durables company, optimizing the market converge may be a very profitable and productive activity. Sales managers of FMCG products can enhance their overall sales by allocating their field resources such as deliver staff to reach the greatest number of customers. Through the process of analysing related documents and object characteristics in FMCG companies, paper aim to build vehicle routing with time window (CVRTW) model to optimize the delivering process, thus satisfying customer demand. To ensure the quality of the results, the model will be solved using the simulated annealing algorithm (SA-algorithm). The overall results support the decision maker the delivery allocation strategy, ensuring the delivery time and client contentment.